Cálculo de la absorción de carbono por ecuaciones alométricas y determinación del factor de equilibrio entre emisión y absorción de carbono en los 11 sumideros del D.M. de Quito - Andrade Calva, Francesca Nathaly (2016)
In this project, the amount of absorbed carbon (carbon stock until year 2015) of 11 sinks located through Quito Metropolitan District (DMQ) was measured. Furthermore, factor of balance between absorption and emission of carbon dioxide (CO2) in the city was calculated. With the aim of know the amount of CO2 that tree species located in DMQ which belong to the eleven sinks being studied, above-ground biomass and below-ground biomass needed to be calculated. Above-ground biomass was estimated by allometric equation of Chave 2005 according to the dasometric variables: diameter breast height (DBH) and wood density (ρ) obtaining a value of 3,050.06 tons. Meanwhile, below-ground biomass obtained a value of 1403.03 tons, as the resulting product of above-ground biomass by the root factor (0.46). To quantify the total amount of carbon absorbed, the total biomass (sum of above-ground and below-ground biomass) was multiplied by the carbon fraction (0.50), giving a resulting value of 2226.55 tons. Absorbed CO2 was calculated multiplying the amount of carbon absorbed with an equivalence factor (3.67), obtaining a value of 8171.42 tons. Finally a balancing factor of 0.0015 was obtained; product of the division of CO2 absorption amount of 8171.42 tons to the amount of CO2 emission of 5,570,436.00 tons. Therefore, Quito emits a higher amount of CO2 compared to the amount that is absorbed by the eleven sinks that the city concentrates.